ผลการจัดกิจกรรมการเรียนรู้ตามแนวคิดวิทยาศาสตร์ เทคโนโลยี สังคมและสิ่งแวดล้อม (STSE) ร่วมกับการออกแบบ infographic โดยใช้ canva ที่มีต่อความตระหนักรู้ต่อสิ่งแวดล้อม ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 : การวิจัยปฏิบัติการ - Thongpak, Nithis; Lalitpasan, Usanee (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
This action research aimed to 1) develop innovative learning management based on science, technology, society and environment (STSE) education with infographic design using Canva affecting environmental awareness, 2) examine the effects of the developed learning management, and 3) examine good practices derived from organizing the developed learning management. The target group consisted of 37 students of Mathayomsuka 1 studying in the second semester of the academic year 2021. Research instruments consisted of 1) lesson plans based on STSE education with infographic design using Canva, 2) a learning management reflection form, and 3) a 30-item assessment form on global warming awareness for lower secondary school students. The research results showed that 1. All elements of lesson plans based on STSE education with infographic design using Canva affecting environmental awareness achieved the highest level of appropriateness. The developed reflection form of learning management could be used as a tool in learning management. 2. The students’ environmental awareness ranged from moderate to very high levels. With the help of Canva, the students were able to create posters to encourage or persuade individuals who view and read them to enhance self-performance and raise environmental awareness. 3. Good practices obtained from the learning management based on STSE education with infographic design using Canva affecting environmental awareness comprised 1) examining documents and research studies comprehensively, 2) employing a variety of processes in analyzing problems and collaborating with teachers from various subjects, 3) reflecting on each step of the six learning management procedures using various approaches, 4) providing feedback or suggestions to improve the products, and 5) publishing the students' results and the teachers' learning management through multiple channels.